Hubungan antara Literasi Keuangan dan Gaya Hidup Pasangan Menikah Muda terhadap Perilaku Keuangan Keluarga di Desa Blado Wetan - Hikam, Ato’illah Shohibul; Nuntupa, Nuntupa; Yuana, Anik Gita (Economic Reviews Journal, 2024)
This research aims to investigate the relationship between financial literacy and the lifestyle of young married couples on family financial behavior in the Blado Wetan Village. This study utilizes a quantitative approach using a questionnaire as a data collection tool. The research sample consists of 35 young married couples randomly selected from the population of Blado Wetan Village. The results of statistical analysis indicate a positive relationship between the level of financial literacy and family financial behavior (r = 0.65, p < 0.05), as well as a negative relationship between the consumptive lifestyle of young married couples and family financial behavior (r = -0.42, p < 0.05). Furthermore, the findings also reveal that financial literacy plays a partial mediating role in the relationship between the lifestyle of young married couples and family financial behavior. The implications of this research underscore the need to enhance financial literacy among young married couples as a strategy to improve family financial well-being, particularly in rural areas like Blado Wetan Village.